Strategi Manajemen Komunikasi Izi Perwakilan Sumatera Selatan Dalam Meningkatkan Eksistensinya di Palembang - Selvia Yolanda Sari; Nurseri Hasnah Nasution; Hidayat HT (ScidacPlus, 2023)
This thesis is entitled Communication Management Strategy of IZI Representative of South Sumatra in Improving the Quality of Its Existence in Palembang. The purpose of this research is to understand the communication management strategy of IZI representatives of South Sumatra in increasing existence in Palembang and to find out the supporting and inhibiting factors. This type of research is field research, with primary and secondary data sources. While data collection techniques obtained by observation, interviews, and documentation. All data will then be analyzed descriptively qualitatively, namely by pouring the results into sentences that are arranged in such a way that they can become neatly arranged sentences. The theory used is the theory according to Parag Diwan which says that communication management is the process of using various communication resources in an integrated manner through the process of planning, organizing, implementing, and controlling the elements of communication to achieve the stated goals. The results of the study show that the communication management strategy used by IZI from South Sumatra in increasing its existence in Palembang is in accordance with the Parag Diwan theory, namely planning, organizing, implementing and evaluating. It's just less than optimal in its application. If it is used optimally, it will be easier for IZI to introduce it to the public and can become even more existent in the future. IZI's supporting factors are official permits from the Ministry of Religion and graduate employees from various campuses. Then the inhibiting factor faced is that IZI is a new institution and the number of employees is small while the range of work is very wide.